The Nazi regime in Lithuania: recovery of agricultural obligations imposed - Braslauskas , Justinas (Genocidas ir rezistencija, 2017)
The purpose of this study is to investigate methods and means of recovery of imposed agricultural obligations. The aim of this paper is to analyse the methods and means for recovery of imposed agricultural obligations in Lithuania, occupied by military forces of Nazi Germany. To achieve the aim, the following objectives have been set: 1) to discuss adaptation of production of agricultural products to meet needs of the war in Lithuania under the Nazi regime; 2) to analyse the methods and means used by occupational Nazi authorities for recovery of agricultural obligations imposed on farmers of Lithuania; 3) to discuss other obligations imposed (other than delivery of agricultural products) on Lithuanian farmers, analyse methods and means for their recovery; 4) submit the exhaustive and reliable statistics on recovery of imposed obligations related to delivery of agricultural products. The topic chosen is a relevant and new one, as this problem has not been presented exhaustively in Lithuanian historiography. First of all, we lack a generalized analysis on the entire Lithuania scale, analysis which must be more detailed, based on archive or reliable statistical data related to practical application of the mechanism of recovery of agricultural obligations (primarily aiming at agricultural products) imposed. This article aims at filling these and other gaps in relevant historiography. During the research the following conclusions have been drawn: 1. In the case of Germany victory in the war, the territories of all Baltic states, including Lithuania, were to be included into the Nazi Reich. During the wartime, the economy of these countries had to serve demands of the Vermacht and meet other Reich needs, irrespective of the interests of the local people and local economies. It had not been planned to create a considerable consumer goods industry. These countries had to be cheap labour sources and base for provision of raw materials, as well as a market for realization of German industry products. 2. The essence of the Nazi agricultural policy in the occupied Lithuania meant a unilateral demand to increase production of basic food products and raw materials in order to provide the German troops as well as local residents and Germans in Germany with food products. The Nazi imposed on farmers various obligations related to agricultural products and various equipment (mobilization of horses with carts and harnesses, obligations of manual work and transport, etc.) 3. Civil occupational Nazi authorities adapted Lithuanian municipal system to meet their agricultural needs during the wartime. The occupational authorities through threatening the officers of Lithuanian municipal system with penalties and negative consequences related to agriculture and farmers, using the help of Lithuanian officers, managed to recover a huge amount of agriculture products from this country agriculture sector. Whereas Lithuanian municipal officers of higher rank were forced to apply constantly the psychological pressure or even coercion on their own subordinates and colleagues of lower rank. 4. In order to recover agricultural obligations fulfilment, the occupants applied both repressive and promoting measures. Among repressive ones, farmer removal from his/her farm should be mentioned as well as requisition of agricultural products, cash penalties, farmers suing with the German Special Court, forcible confining in detention facilities, forced-labour camps or even killing by firing squad. Especially famous for farmers killing by firing squad was H. Wulff, the commissar of Vilnius county district. By killing the farmers, the occupants sought to intimidate the villagers so that they would better fulfil the obligations imposed. 5. To perform recovery of fulfilment of imposed agricultural obligations, the following promoting measures used to be applied: issue of ownership documents, granting the possibility of acquisition of industrial goods, etc. 6. The Nazi failed to convert Lithuanian farmers into obedient executors of alien will. Due to harsh conditions of the wartime and sabotage of Lithuanian farmers in order to protect their farms from the complete deterioration, occupational government of the Nazi each economic year failed to collect from Lithuanian villages planned agricultural products contingencies irrespective of requisition of the large part of agricultural production of this country.